If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = -3x + 2 Reorder the terms: -4 + 2x = -3x + 2 Reorder the terms: -4 + 2x = 2 + -3x Solving -4 + 2x = 2 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + 2x + 3x = 2 + -3x + 3x Combine like terms: 2x + 3x = 5x -4 + 5x = 2 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 5x = 2 + 0 -4 + 5x = 2 Add '4' to each side of the equation. -4 + 4 + 5x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 2 + 4 5x = 2 + 4 Combine like terms: 2 + 4 = 6 5x = 6 Divide each side by '5'. x = 1.2 Simplifying x = 1.2
| (-2)+(-8)+(-4)=a+d | | 2x^2-x+254= | | 2x^2+3x=9x^2-3x-3x+1-x^2 | | v^2-19v+18= | | 0=3900x+217-23.49x^2 | | 7x+6x+4+9=3x+5+9x | | 18x^2-42x=0 | | 4r^2+28r+49= | | (4x-7)=-4 | | 4x+31=91 | | T=3.1-29x | | T=31-29x | | p=2m+2v | | 25a^2-16f^2=0 | | 25r^2+80rd+64d^2=0 | | (2x-1)=7 | | f(-12)=-5x+15 | | 8x+2=5x-8 | | 25r^2-60r+36=0 | | 4z+55z-4=14 | | -6x^2-15x=0 | | 4ln(7x)=8 | | (x+2)(x)(2)=126 | | 15n^2-22np-5p^2=0 | | 10a^3+44a^2-30a=0 | | 5x^2-10x-126=0 | | x-23=31+6x | | 4t^2-24t+32=0 | | (x+2)(x^2)=21 | | 11-1+5x=65x-36 | | 8x-6y=-15 | | 8x-7y=-15 |